PERBANDINGAN PERANCANGAN SUMUR RESAPAN AIR HUJAN MENGGUNAKAN METODE SUNJOTO DAN SNI 03-2453-2002 PADA BANGUNAN KOMERSIAL DI JALAN KALIURANG KM 12 SLEMAN JOGJAKARTA - Prasojo, Rifky Adhi; Astuti, Sri Amini Yuni (Teknisia, 2016)
Imbalance between suction and recharging of groundwater in Kampus Terpadu UII Yogyakarta triggers declined of free water level. The phenomenon can interfere ecosystem balance. Recharging wells are needed to maintain groundwater balance in the surrounding area of Kampus Terpadu UII. Infiltration data as primary data was obtained by using infiltrometer ring. Rainfall data as long as 10 years from narrow rainfall station was used to calculate 5-year return period of rainfall intensity. Both data was used to design recharging wall by using equation presented by Sunjoto method and SNI 03-2453-2002 method. The research results showed that the constant infiltration rate was 0,000017-0,000127 m/second. Circle recharging wells were selected for comparison of both methods effectiveness to collect rainfall run off. Diameter of recharging wall was 1 m, and well depth was 2,5 m. Analyses results showed that number of recharging well designed by using SNI 03-2453-2002 method was more than recharging well designed by using Sunjoto method. Utilization of recharging well can be used to maintain groundwater level. The recharging well can collect rainfall run off more than 98%.